Clinical characteristics and management outcomes of Fournier’s gangrene: a 9-year experience at University of Port Harcourt Teaching Hospital, Choba, Nigeria - Chisor-Wabali, Egbuchilem; Ofuru, Vitalis Obisike; Ekeke, Onyeanunam Ngozi (International Surgery Journal, 2025)
Background: Fournier’s gangrene (FG) is a rapidly progressive, life-threatening necrotizing fasciitis primarily affecting the perineal, genital, and perianal regions. Despite advances in medical care, it remains associated with high morbidity and mortality, especially in resource-limited settings. This study evaluates the clinical characteristics, management strategies, and outcomes of FG at a tertiary care facility in South-South Nigeria using Narayan’s Grading System for severity assessment. Methods: A retrospective review was conducted on 32 male patients treated for FG at the University of Port Harcourt Teaching Hospital between 2013 and 2022. Data on demographics, predisposing factors, disease extent, treatment modalities, and outcomes were collected. Narayan’s Grading System was applied to assess disease severity. Statistical analysis evaluated associations between clinical variables and outcomes. Results: The mean age was 49.7 years. About 25% had predisposing factors, including diabetes and HIV infection. Disease involvement ranged from localized scrotal gangrene to extensive perineal and abdominal wall involvement. All patients received broad-spectrum antibiotics and surgical debridement. The overall mortality rate was 18.8%. Delayed presentation and higher Narayan wound grades were significantly associated with longer healing times. No statistically significant correlation between wound grade and mortality was observed. Conclusions: Early diagnosis and aggressive management, guided by Narayan’s Grading System, are crucial in improving outcomes in Fournier’s gangrene, particularly in low-resource settings where delayed presentation is common. Increased awareness and prompt intervention may reduce the morbidity and mortality associated with this severe condition.